Desired Characteristics of School Administrators under Nong Chok District Bangkok Metropolis - วิชัยรัตน์ ปุณิกา; น้อยมณี นิวัตต์; สุวรรณธารา ภูวนัย (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aimed to (1) study the level of desirable characteristics of school administrators according to the views of teachers in the Nong Chok District Office, Bangkok, and (2) compare the desirable characteristics of school administrators according to the views of teachers in the Nong Chok District Office, Bangkok. The sample group used in this research was 196 teachers in the Nong Chok District Office, Bangkok, academic year 2023, obtained by determining the sample size according to the sample size table of Krejci and Morgan. Then, stratified random sampling was used. The tool used to collect data was a 5-level Likert-type rating scale questionnaire with a reliability of .93. Data were analyzed by testing the differences between the samples using the t-test and a one-way analysis of variance. The research results found that 1) Desired characteristics of school administrators under Nong Chok district Bangkok metropolis, it is at the highest level. When considering each aspect, it was found that the level of desirable characteristics of school administrators was at a high level in every aspect. The average value is ranked first, namely morality, followed by knowledge and ability to perform work. And the aspect that is ranked last is academics. 2) Results of comparing the desired characteristics of Desired characteristics of school administrators under Nong Chok district Bangkok metropolis, classified by gender, educational background, age, and work experience. Overall, the differences were not statistically significant.